Beyond the Story: Evaluating Narrative Model Texts with SFL Transitivity and GBA for Teaching Writing in Secondary Education - Fatresia Tambunan; Wawan Gunawan (ETERNAL (English Teaching Journal), 2026)
This study evaluates the adequacy of the narrative model text “Sangkuriang” from a ninth-grade English textbook in supporting writing skill development under Indonesia’s Emancipated Curriculum. Narrative texts play a significant role in fostering students’ creativity, coherence, and communicative competence. Employing the Genre-Based Approach (GBA) and the Systemic Functional Linguistics (SFL) Transitivity framework, this qualitative study analyzes the text’s generic structure and linguistic features to determine its pedagogical suitability. The findings indicate that the text fulfills the structural components of a narrative genre—orientation, complication, and resolution—and demonstrates a meaningful distribution of material, mental, and relational processes, which are essential for constructing narrative meaning. These linguistic patterns support the development of students’ ability to produce organized and contextually appropriate written texts. The novelty of this study lies in its integrative evaluation of a textbook model text through the combined application of GBA and SFL Transitivity analysis within the framework of the Emancipated Curriculum. Unlike previous research that primarily focuses on students’ writing outcomes or the effectiveness of genre-based instruction, this study critically examines the linguistic adequacy of the model text itself as a pedagogical scaffold. The findings contribute to bridging curriculum goals, genre pedagogy, and functional linguistic analysis in evaluating instructional materials for secondary education.